Sulfonate ligand-induced formation of alkali metal-cucurbit[5]uril-based assemblies - Xu, Jing; Wang, Qi; Ge, Wei Wei; Wu, Dong; Redshaw, Carl; Chen, Kai (CrystEngComm, 2023)
Herein, we report the use of 1,5-naphthalene disulfonic acid (H2NDS) as a structure-directing agent to construct cucurbit[5]uril-based supramolecular assemblies. In order to demonstrate the directing role played by H2NDS. {Q[5]·3[H3O]·3Cl·11H2O} (1) and {Q[5]·H2NDS·13H2O} (2) were separately synthesized by recrystallization of Q[5] from HCl solution in both the absence and the presence of H2NDS. Following the addition of alkali metal cations to the Q[5]-H2NDS system, four novel assemblies with the formulae {[Na2(H2O)2(Q[5])(NDS)0.5]·(NDS)0.5·7H2O} (3), {[K2(H2O)3(Q[5])]·(NDS)·4H2O} (4), {[Rb2(H2O)4(Q[5])]·(NDS)·4H2O} (5) and {[CsK(H2O)5(Q[5])]·(NDS)·4H2O} (6) were obtained. Single-crystal X-ray diffraction studies revealed that all of these metal-containing assemblies have similar general structures to that of 2, with the main differences being the coordination modes of the metal cations in 3-6. Furthermore, relevant experiments revealed that compound 2 can highly selectively detect NFX (norfloxacin) molecules as a ratio type fluorescent probe and also is able to capture acridine red (AR), crystal violet (CV) and methylene blue (MB) from aqueous media and the resulting dye-loaded samples can function as solid fluorescent materials.
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry